2001
DOI: 10.1046/j.1462-2920.2001.00202.x
|View full text |Cite
|
Sign up to set email alerts
|

Direct amplification of nodD from community DNA reveals the genetic diversity of Rhizobium leguminosarum in soil

Abstract: Article:Zeze, A, Mutch, L A and Young, J P W orcid.org/0000-0001- 5259-4830 (2001) ReuseItems deposited in White Rose Research Online are protected by copyright, with all rights reserved unless indicated otherwise. They may be downloaded and/or printed for private study, or other acts as permitted by national copyright laws. The publisher or other rights holders may allow further reproduction and re-use of the full text version. This is indicated by the licence information on the White Rose Research Online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…Laguerre et al (2003), in their ground-breaking study of plant selection of rhizobial genotypes showed that pea plants did not necessarily select the most abundant genotype in the soil; rather, they were able to discriminate among the diversity of soil rhizobial genotypes. This phenomenon had been already described in an earlier clover study by Zeze et al (2001), and in a pea study by Bromfield et al (1995) as well as for other rhizobia-legume systems (Hartmann et al, 1998). As mentioned above, lentil and fava bean reflect in their nodules a rhizobial population that was not significantly different from soil populations.…”
Section: Host Selection Of Genotypes From Those Available In the Soilsupporting
confidence: 70%
See 3 more Smart Citations
“…Laguerre et al (2003), in their ground-breaking study of plant selection of rhizobial genotypes showed that pea plants did not necessarily select the most abundant genotype in the soil; rather, they were able to discriminate among the diversity of soil rhizobial genotypes. This phenomenon had been already described in an earlier clover study by Zeze et al (2001), and in a pea study by Bromfield et al (1995) as well as for other rhizobia-legume systems (Hartmann et al, 1998). As mentioned above, lentil and fava bean reflect in their nodules a rhizobial population that was not significantly different from soil populations.…”
Section: Host Selection Of Genotypes From Those Available In the Soilsupporting
confidence: 70%
“…This amounts to a 15x coverage of one single genome, and would be insufficient to study a whole Rlv population (Jorrín and Imperial, 2015a). Other culture-independent methods, such as direct gene amplification from soil DNA (Zeze et al, 2001, Sarita et al, 2005, Ando et al, 2005, necessarily restrict the analysis to the number of chosen markers and limits any analysis of the entire RL soil population. This leaves culture-dependent methods.…”
Section: Rhizobium Leguminosarum In the Soilmentioning
confidence: 99%
See 2 more Smart Citations
“…trifolii is large and well documented in other parts of the world (Zeze et al, 2001;Duodu et al, 2007). In northern India, in the state of Haryana, extreme conditions of temperature and moisture prevails as rains are very scanty and temperature range is high from -3 to 47 °C (Narula et al, 2013).…”
Section: Introductionmentioning
confidence: 99%